WEST AFRICAN POP ROOTS, by John Collins, Temple University Press, Philadelphia, 1992. - AFRICA O-YE!: A CELEBRATION OF AFRICAN MUSIC, by Graeme Ewens, Da Capo Press, New York, 1991. - BREAKOUT: PROFILES IN AFRICAN RHYTHM, by Gary Stewart, University of Chicago Press, 1992. - wa Mukuna, Kazadi (International Library of African Music, 1996)
pages: 111-115
Keywords: African Music